The concept of happiness : a study of Shihab Al-Din Suhrawardi's Al-Alwah Al 'Imadiyyah - Turan,Emine (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research attempts to study the concept of happiness in the light of Suhrawardi’s views, a Muslim classical philosopher, as discussed in his masterpiece “al-Alwaḥ alʿImadiyyah”. Indeed, the concept of happiness is considered one of the main issues addressed by classical and contemporary Muslim philosophers. Their views on this concept, its ways of achievement and its characteristics vary from one scholar to another. However, most of them explain it within the context of the worldly and the hereafter dimensions. Therefore, the significance of this research relies on the analysis of the views of a classical Muslim philosopher, Suhrawardi, on the concept of happiness as expressed in his book. This research focuses on firstly, the intellectual development of Suhrawardi; secondly, the description of Suhrawardi's masterpiece “al-Alwaḥ al- ʿImadiyyah,”; and lastly, the analysis of Suhrawardi’s philosophical views on happiness. The findings of this research are: firstly, happiness is philosophically supported with evidence from al-Qur'ān and al-Sunnah; secondly, ways to achieve happiness are through reaching maturity, getting rid of the shackles of the material world, and developing divine oriented personality; lastly, the degrees of eternal happiness is attained by beıng close to Allah (S.W.T.), who has sincere conviction in Him, obey Him, and worship Him alone and as such is very close to the divine light. This research adds new insights to the existing body of knowledge related to the philosophical views and interpretation of the concept of happiness.